Further records of phytoseiid (Acari: Mesostigmata: Phytoseiidae) species for Brazil - Barbosa, Marina F. C.; Demite, Peterson R.; Lofego, Antonio C.; Vasconcelos, Geraldo J. N. de; Moraes, Gilberto J. de (Entomological Communications, 2021)
Phytoseiidae Berlese (Acari: Mesostigmata) is a family of predatory mites found mostly on the aerial plant parts. Several phytoseiid species are commercialized as biological control agents. Even though Brazil is the fifth country with the highest number of valid species, knowledge about the phytoseiid fauna in different Brazilian states is highly variable. The objective of this paper is to report unpublished records of phytoseiids on different Brazilian states. The list includes 20 species belonging to 13 genera. New records are reported for 11 states; the largest number of new records is reported for Santa Catarina (7), followed by Paraná (4).